Individualized retrograde endoscopic transoccipital-fourth ventricular-midbrain aqueduct to third and lateral ventriculoperitoneal shunt for complex multilocular hydrocephalus with isolated fourth ventricle: a case report - Wang, Bodong; Wang, Xiaogang; Liu, Qiang; Ma, Ruwen; Zhu, Weijie (Frontiers in Medicine, 2025)
Hydrocephalus is a condition frequently encountered in neurosurgery. An isolated fourth ventricle represents one of the most challenging forms of hydrocephalus. Currently, there are few clinically mature single-session surgical solutions available for the treatment of complex hydrocephalus with an isolated fourth ventricle that exhibits both obstructive and communicating features. Herein, we report a case of complex hydrocephalus with an isolated fourth ventricle treated with an endoscopic transmesencephalic aqueduct retrograde shunt. The patient recovered well postoperatively, with significant improvement in hydrocephalus symptoms. Based on a thorough analysis of the etiology, we suggest that shunt surgery using an endoscopic transoccipital-fourth ventricle-midbrain aqueduct-third ventricle-lateral ventricle retrograde approach can be applied to patients with complex hydrocephalus, using an individualized plan. The successful treatment in our case provides a reference for the management of patients with complex hydrocephalus and an isolated fourth ventricle.